MENAKAR EFEKTIFITAS GURU PAK DALAM MEMELIHARA PERTUMBUHAN IMAN SISWA - Natalia Ayu Larasati; Singgih Prastawa (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The role of the Christian Religious Education teacher has an important role in helping the spiritual growth of students in the educational sphere. The role of the Christian Religion teacher is basically very much needed and has a large correlation to the behavior of students. The role of religious teachers is very important in the life of mankind, especially Christians. Religious education, more specifically Christian religious education is very important to be applied in increasing spiritual potential, thereby helping students to become human beings who believe and obey God. Based on the results of this study, teachers need to pay attention to every day behavior of their students and always be wise and act especially in terms of the role of the Christian Religion teacher.